2014
DOI: 10.1007/s11999-013-3400-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Preoperative American Society of Anesthesiologists Score Relate to Complications After Total Shoulder Arthroplasty?

Abstract: Background For hip and knee arthroplasties, an Ameri-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 48 publications
2
28
1
1
Order By: Relevance
“…The degree to which this issue influenced our results is unclear, although it has been reported that the majority of common diagnoses are comorbidities rather than adverse events [15,30,36]. Fourth, the NHDS enabled only ascertainment of inpatient outcomes, and thus postdischarge complications [24,40,58]. Finally, we did not perform any clinical data abstraction from medical records, which is considered the gold standard risk adjustment method in these comparisons [10]; thus, we were able to compare the Charlson and Elixhauser measures only for their relative performance.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The degree to which this issue influenced our results is unclear, although it has been reported that the majority of common diagnoses are comorbidities rather than adverse events [15,30,36]. Fourth, the NHDS enabled only ascertainment of inpatient outcomes, and thus postdischarge complications [24,40,58]. Finally, we did not perform any clinical data abstraction from medical records, which is considered the gold standard risk adjustment method in these comparisons [10]; thus, we were able to compare the Charlson and Elixhauser measures only for their relative performance.…”
Section: Discussionmentioning
confidence: 93%
“…Patients undergoing orthopaedic surgery often have multiple coexisting medical conditions (comorbidities) [13,21,24,28,39,45,58]. Preoperative risk assessment can help with decision-making and management strategies [11,37,50].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Patients with a higher comorbidity burden may have complications stemming directly from their underlying medical disease and are also perhaps more susceptible to complications related to the fracture and subsequent surgery. Increased ASA class indicates severe underlying medical disease, which has been previously found to be associated with increased risk of adverse events after many types of orthopaedic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, because we risk adjusted using administrative data alone, we were unable to include other clinically important parameters such as the American Society of Anesthesiologists score, the Frailty Index developed by the Canadian Study of Health and Aging, the Geriatric Index of Comorbidity, the Total Illness Burden Index, or the Functional Comorbidity Index, which may have enhanced model performance. [48][49][50][51][52] Finally, we were only able to compare the Charlson and Elixhauser comorbidity scores in terms of their relative predictive performance, as we did not perform any clinical data abstraction from medical records--the gold-standard risk adjustment method in these comparisons. 20,53 In this study of nationally representative data collected between 2002 and 2011, the Elixhauser comorbidity-based measure outperformed the Charlson index in predicting inpatient mortality after proximal humerus fracture.…”
Section: Discussionmentioning
confidence: 99%